PENGARUH MOTIVASI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN YAYASAN SAHABAT YATIM INDONESIA CABANG TANGERANG SELATAN - Septiana, Fadhila Alroof; Sudarso, Eko (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to examine the influence of motivation and organizational culture on employee performance at the Indonesian Yatim Friends Foundation, South Tangerang Branch. A quantitative research method was used, with survey data collected from 84 respondents through structured questionnaires. The independent variables in this study are motivation (X₁) and organizational culture (X₂), while the dependent variable is employee performance (Y). Validity testing showed all questionnaire items to be valid, with r count > 0.214. Reliability testing produced Cronbach’s Alpha scores of 0.848 for motivation, 0.771 for organizational culture, and 0.821 for employee performance, indicating reliable instruments.The multiple linear regression analysis yielded the following equation:Y = 17.175 + 0.295X₁ + 0.269X₂ The coefficient of determination (R²) was 0.230, meaning motivation and organizational culture together explain 23.0% of the variance in employee performance.Partially, motivation significantly affects performance (t count = 3.012 > 1.991; sig = 0.003 < 0.05), while organizational culture also has a significant effect (t count = 2.458 > 1.991; sig = 0.016 < 0.05). Simultaneously, the F-test shows F count = 12.112 > F table = 2.72, with a significance of 0.000